THE RELATIONSHIP BETWEEN THE LEVEL OF INVOLVEMENT IN LITERACY PROGRAMS AND THE INCREASE IN KNOWLEDGE OF THE KARO COMMUNITY IN KABANJAHE - Fitri Ikhsani Hasibuan; Retno Sayekti (SOSIOEDUKASI, 2026)
This research examines the relationship between community involvement in literacy programs and the subsequent increase in public knowledge among the Karo community in Kabanjahe. Using a quantitative correlation approach, data was collected from local residents who actively participated in core programs organized by the Karo Regency Library and Archives Department, such as Kilap Pustaka and Safari Literacy. All research instruments were validated, proven reliable, and met assumptions of normality before analysis. These findings show that the level of community involvement in various literacy activities is relatively high. Correspondingly, their knowledge and understanding after participating in these programs shows a substantial increase, including in the good category. Correlation analysis confirmed a statistically significant and positive moderate strength relationship between the two variables. This direct relationship implies that higher and more active participation in literacy initiatives leads to a greater expansion of knowledge and insight into everyday life. Consequently, this research concludes that actively involving citizens in social inclusion-based literacy programs serves as an effective mechanism for sharpening thinking skills, broadening perspectives, and cultivating strong and sustainable learning habits in society.